Vanadium salts versus diabetes: An overview - Mishra S.K.; Kumar A.; Chaturvedi R.K.; Pandeya S.N. (My University, 2025)
Vanadium is an ultra trace element, widely distributed in the nature and its compounds would closely mimic the physiological action of insulin by initial entry into the portal system. This mini review summarized the latest advancements in this field, considering the vanadium compounds effective in organic or inorganic forms. The major concern related to the use of vanadium salts is the safety profile. Vanadate has insulin-like effects on the metabolism of glucose both in vivo and in vitro in various tissues. Vanadium salts such as Na3VO4 NaVO3, VOSO4, VO (acac)2, and VO (Et-acac)2 mimic several of the metabolic and growth-promoting effects of insulin. Some traditional medicines from a number of plants and plant products with antidiabetic activity also show great promise. Some studies have suggested that vanadium compounds help to normalize blood glucose levels in people with both type I and type II diabetes. © 2010 EManuscript Technologies. All rights reserved.